Water-energy-food-ecosystem nexus approach presents a solution for transboundary resources management in Nepal - Koirala, Sanju; Niroula, Aayush; Mishra, Anuj; Subedi, R.; Pradhan, Melissa (International Water Management Institute, 2025)
Stakeholders in the Rangun watershed in Nepal’s Mahakali-Karnali River Basin illustrate how a holistic approach across the Water-Energy-Food-Ecosystem Nexus can offer scalability for broader cross-border challenges.